Silicon-based composite material, preparation method thereof, negative electrode sheet and secondary battery

CN122659094APending Publication Date: 2026-08-28LI ZHEN DIAN ZI KE JI (KUN SHAN) YOU XIAN GONG SI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610967516.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

例如,在嵌锂膨胀时各个方向受力不均,颗粒易被撑破,影响循环性能;制备极片辊压时,因颗粒相互搭接受剪切力作用,更容易被压碎,导致首效降低;颗粒间空隙大,压实密度低,不利于提高电池能量密度,也难以解决电芯K值恶化的情况

Benefits of technology

[0031]In the silicon-based composite material described in this invention, the distribution density gradient of silicon particles within the spherical framework decreases while the particle size gradient increases. This utilizes the isotropic expansion characteristic to achieve a more uniform volume change during charging and discharging, significantly reducing the volume expansion rate. This improves the stability of the silicon-based composite material and the cycle life of the battery. Furthermore, the gradient silicon particle distribution promotes uniform lithiation, ensuring continuous internal ion diffusion paths and enabling rapid lithium-ion diffusion, thereby enhancing the capacity and rate performance of the silicon-based composite material. In addition, the spherical framework of this invention provides a uniform pore distribution (such as micropores and mesopores) and surface active sites. Combined with the gradient design, it avoids localized volume expansion caused by silicon particle agglomeration. Simultaneously, the spherical framework structure enhances the compressive strength and impact resistance of the silicon-based composite material and, in conjunction with the coating layer, further reduces volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122659094A_ABST
    Figure CN122659094A_ABST
Patent Text Reader

Abstract

The application provides a silicon-based composite material and a preparation method thereof, a negative electrode sheet and a secondary battery. The silicon-based composite material comprises a core and a coating layer covering the outer surface of the core. The core comprises a spherical framework and silicon particles. The spherical framework is a porous structure, and part or all of the silicon particles are accommodated in the porous structure of the spherical framework. The distribution density of the silicon particles decreases in a gradient from the center of the spherical framework to the outer surface of the spherical framework, and the particle size of the silicon particles increases in a gradient. The density and particle size of the silicon particles in the silicon-based composite material are distributed in a gradient, the expansion stress distribution of the silicon particles is optimized, the volume expansion rate of the silicon particles is reduced, the continuity of the ion path is maintained, and thus the initial efficiency, cycle life and rate performance of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, specifically a silicon-based composite material and its preparation method, a negative electrode sheet, and a secondary battery. Background Technology

[0002] With the rapid development of consumer electronics, electric vehicles, and electrochemical energy storage industries, the market demand for high-energy-density lithium-ion batteries is becoming increasingly urgent. Traditional graphite anode materials, with a theoretical specific capacity of only 372 mAh / g, are insufficient to meet the requirements of high-energy-density lithium-ion batteries. Elemental silicon, due to its abundant reserves on Earth, theoretical specific capacity as high as 4200 mAh / g, and high lithium intercalation potential, has attracted much attention. However, silicon anode materials suffer from problems such as intrinsically low conductivity, significant volume expansion after lithium intercalation, material fragmentation, performance degradation after multiple cycles, and capacity loss due to SEI formation.

[0003] With continuous technological innovation, the problems of silicon anode materials are gradually being solved, and they have gradually become the next-generation lithium battery anode material widely recognized in the market. However, the porous carbon substrates commonly used in third-generation vapor-deposited silicon-carbon materials are mostly irregular in shape, resulting in many drawbacks for silicon-carbon anode materials prepared from them. For example, during lithium intercalation and expansion, the force is uneven in all directions, making the particles easily broken and affecting cycle performance; during the preparation of electrode sheets by rolling, the particles are more easily crushed due to the shear force acting on each other, leading to a reduction in initial efficiency; the large gaps between particles and the low compaction density are not conducive to improving battery energy density and also make it difficult to solve the problem of cell K-value deterioration. Summary of the Invention

[0004] The purpose of this invention is to provide a silicon-based composite material and its preparation method, a negative electrode sheet and a secondary battery. The silicon-based composite material has a gradient distribution of silicon particle density and particle size, which optimizes the expansion stress distribution of silicon particles, reduces the volume expansion rate of silicon particles, and maintains the continuity of ion pathways, thereby improving the initial efficiency, cycle life and rate performance of the secondary battery.

[0005] To achieve this objective, the embodiments of the present invention employ the following technical solutions:

[0006] In a first aspect, embodiments of the present invention provide a silicon-based composite material, the silicon-based composite material comprising a core and a coating layer covering the outer surface of the core;

[0007] The core includes a spherical framework and silicon particles, wherein the spherical framework has a porous structure, and some or all of the silicon particles are housed within the porous structure of the spherical framework.

[0008] From the center of the spherical skeleton to the outer surface of the spherical skeleton, the distribution density gradient of the silicon particles decreases, while the particle size gradient of the silicon particles increases.

[0009] Furthermore, the spherical framework is divided into an inner ring region and an outer ring region covering the surface of the inner ring region. The distribution density of silicon particles in the inner ring region is 1.5 to 3 times that of the distribution density of silicon particles in the outer ring region.

[0010] Furthermore, the particle size of the silicon particles in the inner ring region is ≤2nm, the particle size of the silicon particles in the outer ring region is ≤3nm, and the ratio of the particle size of the silicon particles in the inner ring region to the particle size of the silicon particles in the outer ring region is 0.30~0.8.

[0011] Furthermore, in the spherical skeleton, the volume ratio of the inner ring region is 30% to 70%.

[0012] Furthermore, the distribution density of silicon particles in the inner ring region is 1.8 to 2.5 times that of the distribution density of silicon particles in the outer ring region.

[0013] Furthermore, the particle size of the silicon particles in the inner ring region is 1.2 nm to 1.8 nm, the particle size of the silicon particles in the outer ring region is 2.2 nm to 3.0 nm, and the ratio of the particle size of the silicon particles in the inner ring region to the particle size of the silicon particles in the outer ring region is 0.40 to 0.70.

[0014] Furthermore, the particle size of the silicon particles is 1.30 nm to 3.00 nm.

[0015] Furthermore, the spacing between the silicon particles is 0.5 nm to 2.0 nm.

[0016] Furthermore, the spherical framework includes any one or a combination of at least two of the following: spherical carbon materials, spherical metal oxides, conductive polymer spheres, spherical organic frameworks, or spherical composite materials.

[0017] Furthermore, the particle size D50 of the spherical skeleton is 1μm~12μm.

[0018] Furthermore, the coating layer comprises any one or a combination of at least two of carbon, oxides, halides, lithium-containing compounds, or polymers.

[0019] Furthermore, the thickness of the coating layer is 20nm~100nm.

[0020] Furthermore, the sphericity of the silicon-based composite material is ≥70%.

[0021] Furthermore, the repose angle of the silicon-based composite material is ≤38°.

[0022] Furthermore, the silicon content in the silicon-based composite material is 10wt%~80wt%.

[0023] Secondly, embodiments of the present invention provide a method for preparing a silicon-based composite material as described in the first aspect, the method comprising the following steps:

[0024] A spherical framework is placed in a reactor, and a silicon source is introduced into the reactor for at least two stages of deposition. The silicon source enters the porous structure of the spherical framework and is transformed into silicon particles to obtain the core.

[0025] The core is placed in a reactor, a coating source is introduced, and coating deposition is performed to form a coating layer on the outer surface of the core, thus obtaining the silicon-based composite material.

[0026] Furthermore, the at least two deposition stages include sequentially performing a first deposition stage and a second deposition stage; the temperature of the first deposition stage is 350℃~500℃, the silicon source flow rate is 0.8L / min~2.2L / min, and the deposition time is 100min~500min; the temperature of the second deposition stage is 500℃~700℃, the silicon source flow rate is 0.2L / min~1.2L / min, and the deposition time is 50min~300min; wherein, the temperature, silicon source flow rate, and deposition time of the first deposition stage are not exactly the same as those of the second deposition stage.

[0027] Furthermore, the temperature of the first deposition stage is lower than that of the second deposition stage, and / or the silicon source flow rate of the first deposition stage is higher than that of the second deposition stage, and / or the deposition time of the first deposition stage is longer than that of the second deposition stage.

[0028] Thirdly, embodiments of the present invention provide a negative electrode sheet, the negative electrode sheet comprising a silicon-based composite material as described in the first aspect, or a silicon-based composite material prepared by the preparation method described in the second aspect.

[0029] Fourthly, embodiments of the present invention provide a secondary battery, the secondary battery comprising a silicon-based composite material as described in the first aspect, or a silicon-based composite material prepared by the preparation method described in the second aspect, or a negative electrode sheet as described in the third aspect.

[0030] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0031] In the silicon-based composite material described in this invention, the distribution density gradient of silicon particles within the spherical framework decreases while the particle size gradient increases. This utilizes the isotropic expansion characteristic to achieve a more uniform volume change during charging and discharging, significantly reducing the volume expansion rate. This improves the stability of the silicon-based composite material and the cycle life of the battery. Furthermore, the gradient silicon particle distribution promotes uniform lithiation, ensuring continuous internal ion diffusion paths and enabling rapid lithium-ion diffusion, thereby enhancing the capacity and rate performance of the silicon-based composite material. In addition, the spherical framework of this invention provides a uniform pore distribution (such as micropores and mesopores) and surface active sites. Combined with the gradient design, it avoids localized volume expansion caused by silicon particle agglomeration. Simultaneously, the spherical framework structure enhances the compressive strength and impact resistance of the silicon-based composite material and, in conjunction with the coating layer, further reduces volume expansion. Attached Figure Description

[0032] Figure 1 This is a SEM image of the silicon-based composite material described in Example 1 of the present invention.

[0033] Figure 2 This is a SEM image of the silicon-based composite material described in Comparative Example 1 of the present invention.

[0034] Figure 3 The images show the XRD patterns of the silicon-based composite materials described in Embodiment 1, Comparative Example 1, and Comparative Example 2 of the present invention.

[0035] Figure 4 The diagram shows the rate performance of the secondary battery prepared using the silicon-based composite material described in Example 1 and Comparative Example 1 of this invention.

[0036] Figure 5 The diagram shows the cycle performance of the secondary batteries prepared using the silicon-based composite materials described in Example 1 and Comparative Example 1 of this invention.

[0037] Figure 6 This is a SEM-EDS line scan image of the silicon-based composite material described in Example 1 of the present invention. Detailed Implementation

[0038] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0039] In one specific embodiment, a silicon-based composite material is provided, the silicon-based composite material comprising a core and a coating layer covering the outer surface of the core;

[0040] The core includes a spherical framework and silicon particles, wherein the spherical framework has a porous structure, and some or all of the silicon particles are housed within the porous structure of the spherical framework.

[0041] From the center of the spherical skeleton to the outer surface of the spherical skeleton, the distribution density gradient of the silicon particles decreases, while the particle size gradient of the silicon particles increases.

[0042] The silicon-based composite material of the present invention includes a spherical skeleton (spherical or near-spherical), silicon particles, and a coating layer. The spherical skeleton and silicon particles form a core, and the coating layer covers the outer surface of the core. The spherical skeleton has a porous structure. All or part of the silicon particles are located inside the spherical skeleton. Furthermore, the silicon particles have a density gradient distribution and a particle size gradient distribution in the spherical skeleton. Specifically, since the internal channels of the spherical framework are more conducive to silicon source penetration and provide more confined deposition sites, while the outer ring is closer to the electrolyte contact interface, it is necessary to reduce the silicon particle distribution density and appropriately increase the buffer space between silicon particles. Therefore, in the spherical framework of the present invention, the distribution density gradient of the silicon particles decreases from the inside to the outside, while the particle size gradient increases. This not only utilizes the isotropic expansion characteristics to achieve a more uniform volume change of silicon during charging and discharging, significantly reducing the volume expansion rate of silicon-based composite materials, but also optimizes the spacing between silicon particles, maintains the continuity of ion paths, and makes the internal ion diffusion path continuous, achieving rapid lithium-ion diffusion. Therefore, the gradient design of silicon particles in the spherical framework of the present invention makes the silicon dispersion at the atomic to nanoscale more uniform, effectively avoiding silicon breakage and local stress concentration during cycling, and also making the internal ion diffusion path continuous, thereby improving the capacity, first efficiency, cycle performance, and rate performance of the secondary battery.

[0043] Furthermore, the spherical skeleton described in this invention possesses radial symmetry and equiaxedness. The radial symmetry provides a uniform distribution of pores (such as micropores and mesopores) and surface active sites. Combined with gradient design, it avoids local volume expansion caused by silicon particle agglomeration. At the same time, the equiaxedness of the spherical skeleton enables the silicon-based composite material to have higher compressive strength and impact resistance, and works with the coating layer to further suppress expansion.

[0044] In one specific embodiment, the spherical skeleton is divided into an inner ring region and an outer ring region covering the surface of the inner ring region. The distribution density of silicon particles in the inner ring region is 1.5 to 3 times that of the distribution density of silicon particles in the outer ring region. For example, it can be 1.5 times, 1.7 times, 1.9 times, 2.1 times, 2.3 times, 2.5 times, 2.7 times, 2.9 times, or 3 times, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0045] The silicon particle distribution density in the inner ring region of this invention is 1.5 to 3 times (preferably 1.8 to 2.5 times) that in the outer ring region, to avoid an excessive difference in the distribution density of the inner and outer silicon particles. If the distribution density of the inner and outer silicon particles is too different, it will lead to uneven stress distribution, excessive expansion difference, excessive expansion of the inner ring region, stress concentration, damage to ion transport channels, and interface instability, which will affect the first efficiency and cycle performance of the secondary battery. This invention controls the silicon particle distribution density of the inner and outer rings within a certain multiple range, which utilizes the gradient of high distribution density in the inner ring and low distribution density in the outer ring for deep ion transport, while avoiding structural risks caused by excessively high silicon density in the inner ring.

[0046] The silicon particle distribution density in the inner ring region of this invention is 1.5 to 3 times that in the outer ring region. This is verified by cross-sectional SEM-EDS line scanning of silicon concentration. The silicon atom concentration ratio between the inner and outer ring regions is ≥1.5, and the full width at half maximum (FWHM) of the 0.45V dQ / dV peak is ≥0.05V, indicating uniform lithiation and further improvement in first-efficiency, cycle life, and rate retention.

[0047] In one specific embodiment, the particle size of the silicon particles in the inner ring region is ≤2nm (preferably 1.2nm~1.8nm), for example, it can be 2nm, 1.8nm, 1.6nm, 1.4nm, 1.2nm or 1nm; the particle size of the silicon particles in the outer ring region is ≤3nm (preferably 2.2nm~3.0nm), for example, it can be 3nm, 2.8nm, 2.5nm, 2.2nm, 2.0nm, 1.8nm or 1.5nm; and the ratio of the particle size of the silicon particles in the inner ring region to the particle size of the silicon particles in the outer ring region is 0.3~0.8 (preferably 0.40~0.70), for example, it can be 0.8, 0.7, 0.6, 0.5, 0.4 or 0.3, but is not limited to the listed values, and other unlisted values ​​within the value range are also applicable.

[0048] In this invention, the silicon particles in the inner ring region are smaller in size, while those in the outer ring region are relatively larger, and the ratio between the two is within a specific range. Otherwise, if the difference in particle size is too small, the particle size gradient distribution effect will be insignificant, resulting in an indistinct particle size gradient between the inner and outer rings. This makes it difficult to effectively disperse the lithium intercalation expansion stress, and the material is still prone to local stress concentration and increased interfacial side reactions during cycling. However, if the difference in particle size between the silicon particles in the inner ring region and the outer ring region is too large, it will lead to a large difference in the reactivity and degree of lithiation between the inner and outer rings, which can easily cause uneven local lithiation, discontinuous ion transport paths, and unbalanced stress distribution within the particles, thereby affecting rate performance and cycling stability.

[0049] In one specific embodiment, the volume ratio of the inner ring region in the spherical skeleton is 30% to 70%, for example, it can be 30%, 40%, 50%, 60% or 70%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable, preferably 40% to 60%.

[0050] This invention divides the spherical framework into two regions: a core, known as the inner ring region, and an area outside the core, known as the outer ring region. The volume ratio of the inner ring region defined by this invention represents the proportion of the inner and outer ring regions within the spherical framework. This affects the density and size gradient distribution of the silicon particles. If the volume ratio of the inner ring region is too small, the volume ratio of the outer ring region will be too large, resulting in insufficient effective silicon deposition area in the inner ring region, making it difficult to form a significant silicon density gradient with higher density inside and lower density outside, thus affecting the dispersion of expansion stress. If the volume ratio of the inner ring region is too large, the volume ratio of the outer ring region will be too small, resulting in insufficient buffer space and protective coating in the outer ring region. This makes it easier for the outer silicon particles to come into direct contact with the electrolyte, leading to increased side reactions, reduced first-time efficiency, and decreased cycle stability.

[0051] In some embodiments, the silicon particles are crystalline silicon and / or amorphous silicon.

[0052] In one specific embodiment, the particle size of the silicon particles is 1.30nm to 3.00nm, for example, it can be 1.30nm, 1.50nm, 2.0nm, 2.25nm, 2.5nm, 2.75nm or 3.00nm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0053] Based on the condition that the particle size of silicon particles in the inner ring region is ≤2nm and the particle size of silicon particles in the outer ring region is ≤3nm, the particle size of silicon particles mentioned here in this invention refers to the range that the particle size of all silicon particles in the inner and outer ring regions meets; the particle size of silicon particles within a specific range can further reduce the expansion rate of silicon particles and reduce the risk of silicon particle breakage during cycling.

[0054] The particle size of the silicon particles described in this invention can be determined by aberration-corrected electron microscopy (AC-TEM).

[0055] In one specific embodiment, the spacing between the silicon particles is 0.5nm to 2.0nm, for example, it can be 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm or 2nm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0056] The spacing between silicon particles described in this invention is within a specific range, which not only provides space for the expansion of silicon particles but also ensures the continuity of the ion diffusion path.

[0057] The spacing between the silicon particles described in this invention can be characterized and determined by aberration-corrected electron microscopy (AC-TEM).

[0058] In one specific embodiment, the spherical framework includes any one or a combination of at least two of the following: spherical carbon materials (e.g., spherical porous carbon, spherical graphite, spherical hard carbon, spherical soft carbon, spherical graphene, spherical carbon nanotubes, spherical commercial carbon black, etc.), spherical metal oxides (e.g., spherical copper oxide, spherical copper foam, spherical TiO2, spherical SnO2), conductive polymer spheres, spherical organic frameworks (e.g., spherical metal-organic frameworks, spherical covalent organic frameworks), or spherical composite materials (e.g., spherical metal composite carbon materials, spherical soft and hard carbon materials). In addition, it can also be a novel spherical carbon material with a special pore structure, such as ordered mesoporous carbon spheres with a specific pore size distribution, or a spherical structure formed by the self-assembly of carbon nanotubes / graphene. It can also be modified by introducing groups, etching to form defect sites, element doping, etc.

[0059] In some embodiments, the porous structure of the spherical skeleton is any one or a combination of at least two of the following: straight cylindrical holes, conical holes, slit holes, void holes, or slit holes.

[0060] In one specific embodiment, the particle size D50 of the spherical skeleton is 1μm to 12μm, for example, it can be 1μm, 3μm, 5μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0061] This invention employs a spherical skeleton with a specific particle size D50, which facilitates the introduction of silicon particles and ensures that the particle size D50 of the silicon-based composite material is within a suitable range.

[0062] In one specific embodiment, the coating layer comprises any one or a combination of at least two of carbon, oxides, halides, lithium-containing compounds, or polymers.

[0063] The coating layer described in this invention is not limited to a carbon coating layer, but may include carbon, oxides, halides, lithium-containing compounds, polymers, and modified doped materials, which can synergistically suppress silicon particle expansion with the spherical framework, while also improving the conductivity of silicon-based composite materials.

[0064] In one specific embodiment, the thickness of the coating layer is 20nm~100nm, for example, it can be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0065] The thickness of the coating layer described in this invention affects the suppression effect on the core and also affects the capacity utilization of the silicon-based composite material, preferably within a specific range.

[0066] In one specific embodiment, the sphericity of the silicon-based composite material is ≥70%, for example, it can be 70%, 75%, 80%, 85%, 90% or 95%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0067] The sphericity described in this invention is a geometric parameter that quantitatively characterizes how close a particle is to an ideal sphere. The larger the sphericity, the closer it is to an ideal sphere.

[0068] In one specific embodiment, the repose angle of the silicon-based composite material is ≤38°, for example, it can be 38°, 35°, 30°, 25°, 20° or 15°, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0069] The angle of repose described in this invention is defined as the angle between the surface (free inclined plane) of the accumulation material and the horizontal plane when granular material is poured onto a horizontal surface and piled into a cone. The smaller the angle of repose, the stronger the flowability of the particles. Therefore, the angle of repose of the silicon-based composite material described in this invention corresponds to the flowability of the particles and is related to the processing performance of the battery cell electrode sheet.

[0070] In one specific embodiment, the particle size D50 of the silicon-based composite material is 1μm to 15μm, for example, it can be 1.02μm, 3μm, 5μm, 7μm, 9μm, 12μm, 14μm or 15μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0071] In some embodiments, the specific surface area of ​​the silicon-based composite material is ≤10.0 m². 2 / g, for example, could be 10.0m 2 / g, 9.0m 2 / g, 8.0m 2 / g, 7.0m 2 / g, 6.0m 2 / g, 5.0m 2 / g, 4.0m 2 / g or 3.0m 2 / g, but not limited to the listed values, other unlisted values ​​within the range also apply.

[0072] In some embodiments, the tap density of the silicon-based composite material is 1.0 g / cm³. 3 ~1.5g / cm 3 For example, it could be 1.0 g / cm³. 3 1.1g / cm 3 1.2g / cm 3 1.3g / cm 3 1.4g / cm 3 Or 1.5g / cm 3 However, this does not limit the listed values; other unlisted values ​​within the range are also applicable.

[0073] In some embodiments, the compaction density of the silicon-based composite material can be 1.2 g / cm³. 3 ~2.0g / cm 3 For example, it could be 1.2 g / cm³. 3 1.3g / cm 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.7g / cm 3 1.8g / cm 3 1.9g / cm 3 Or 2.0g / cm 3 However, this does not limit the listed values; other unlisted values ​​within the range are also applicable.

[0074] In some embodiments, the pH value of the silicon-based composite material is 4 to 10, for example, it can be 4, 5, 6, 7, 8, 9 or 10, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0075] The powder resistivity of the silicon-based composite material described in this invention is a key parameter for evaluating the electrochemical performance of the material. In some embodiments, the 10MPa powder resistivity of the silicon-based composite material (which can be measured by a powder resistivity tester) is ≤60Ω·cm, for example, it can be 60Ω·cm, 50Ω·cm, 40Ω·cm, 30Ω·cm, 20Ω·cm or 10Ω·cm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0076] The gas production of the silicon-based composite material described in this invention affects the slurry preparation process and high-temperature performance of the battery cell. The gas production can be measured using the Archimedes density method (test temperature: 45±0.5℃). In some embodiments, the medium for the test method is water. The gas production of the powder at high temperature for 24 hours can be ≤0.2mL / g, for example, 0.15mL / g, 0.10mL / g, or 0.05mL / g; the gas production of the silicon-based composite material powder at high temperature for 48 hours can be ≤0.5mL / g, for example, 0.4mL / g, 0.3mL / g, or 0.2mL / g; and the gas production of the silicon-based composite material powder at high temperature for 72 hours can be ≤0.8mL / g, for example, 0.6mL / g, 0.4mL / g, or 0.2mL / g. In other embodiments, the medium for the test method is an alkaline solution. The gas production of the powder at high temperature for 6 hours can be ≤0.08 mL / g, for example, 0.06 mL / g, 0.04 mL / g, or 0.02 mL / g; the gas production of the powder at high temperature for 12 hours can be ≤0.20 mL / g, 0.15 mL / g, 0.10 mL / g, or 0.05 mL / g; the gas production of the powder at high temperature for 24 hours can be ≤0.50 mL / g, for example, ≤0.40 mL / g, 0.25 mL / g, or 0.10 mL / g, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0077] In one specific embodiment, the silicon content in the silicon-based composite material is 10wt% to 80wt%, for example, it can be 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0078] In the silicon-based composite material described in this invention, the silicon content affects the overall performance of the material, especially its capacity, which is also related to the energy density of the battery cell. Preferably, within a specific range, the silicon content can be measured by high-temperature calcination in an air, oxygen, or mixed gas atmosphere or by thermogravimetric analysis.

[0079] The presence of impurities such as iron, chromium, cobalt, nickel, zinc, copper, calcium, manganese, sodium, and potassium in the silicon-based composite material described in this invention can impair cell performance in three directions: structural damage (expansion / fracture), electrochemical interference (impedance / instability of solid electrolyte interface film), and safety risks (gas generation / thermal runaway). In some embodiments, the iron content in the silicon-based composite material is ≤50ppm, chromium content is ≤50ppm, cobalt content is ≤40ppm, nickel content is ≤40ppm, zinc content is ≤40ppm, calcium content is ≤250ppm, manganese content is ≤40ppm, sodium content is ≤100ppm, and potassium content is ≤100ppm.

[0080] In some embodiments, the silicon-based composite material has a 1.5V initial reversible capacity ≥1600mAh / g, for example, 1800mAh / g, 1900mAh / g, 2000mAh / g, 2200mAh / g, or 2400mAh / g; correspondingly, its 1.5V initial coulombic efficiency ≥89.0%, for example, 92.0%, 94.0%, or 96.0%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0081] The 1.5V first reversible capacity of the silicon-based composite material described in this invention is closely related to the voltage plateau capacity of the battery cell and is also related to the improvement of the battery cell's energy density. This invention provides a gradient distribution of silicon particle density and particle size to promote uniform lithiation and make the internal ion diffusion path continuous, thereby enabling the 1.5V first reversible capacity of the silicon-based composite material to be ≥1700mAh / g.

[0082] In some embodiments, the first coulombic efficiency of the silicon-based composite material at 0.8V is ≥79%, for example, it can be 79%, 82%, 84% or 86%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0083] The initial coulombic efficiency of the silicon-based composite material described in this invention is related to the initial energy density and cycle life of the cell. A decrease in initial efficiency will lead to a decrease in the full cell capacity, requiring additional cathode material to compensate, which increases costs. Moreover, a low initial efficiency will also exacerbate the continuous consumption of active lithium during cycling. The gradient design of silicon particles described in this invention reduces silicon exposure side reactions and helps to improve the initial efficiency.

[0084] In some embodiments, the dQ / dV value corresponding to the 0.45V voltage plateau of the silicon-based composite material is ≤1.8, for example, it can be 1.8, 1.7, 1.6, 1.5 or 1.4; and the full width at half maximum (FWHM) of its characteristic peak is ≥0.05V, for example, it can be 0.06V, 0.08V, 0.10V or 0.15V, but is not limited to the listed values, and other unlisted values ​​within the value range are also applicable.

[0085] The 0.45V voltage plateau characteristic peak of the silicon-based composite material in the dQ / dV curve of the present invention corresponds to the phase transition initiation point of the lithiation process. Its dQ / dV value and full width at half maximum (FWHM) can reflect the floating silicon on the material surface and the uniformity of lithiation. The gradient distribution of silicon particles in the present invention promotes the broad peak feature, indicating uniform lithiation.

[0086] In some embodiments, the silicon-based composite material has a 100-cycle retention rate of ≥83.00%, such as 85.00%, 90.00%, or 95.00%, but is not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0087] The cycle retention rate of the silicon-based composite material described in this invention is a core indicator for evaluating the practicality of silicon-based composite materials, and its level directly determines the cycle life and reliability of the material. This invention achieves stress dispersion and expansion control through the gradient distribution of silicon particle density and particle size, which significantly improves the cycle stability of the material.

[0088] In some embodiments, the capacity retention of the silicon-based composite material at high 3C rates is increased to ≥63.20%, for example, it may be 65.00%, 70.00% or 75.00%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0089] The 3C high-rate capacity retention of the silicon-based composite material described in this invention mainly reflects its structural stability, interface dynamics, and electron / ion transport efficiency under high-power charging and discharging scenarios. The gradient distribution design of silicon particle density and particle size described in this invention ensures the continuity of the internal ion diffusion path, realizes rapid lithium-ion diffusion, and thus improves the rate performance of the material.

[0090] In some embodiments, the electrode expansion rate of the silicon-based composite material after 50 cycles is ≤55%, for example, it can be 55%, 50%, 45% or 40%, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0091] Since the volume expansion of silicon during cycling can cause structural damage and affect long-term cycling stability and safety performance, the cycling expansion of the electrode is a key limiting indicator for the commercial application of materials. This invention effectively reduces expansion stress by gradient distribution of silicon particle density and particle size, thus significantly reducing the expansion rate of the electrode.

[0092] The present invention also provides a method for preparing the silicon-based composite material, the method comprising the following steps:

[0093] S1: Place the spherical skeleton in the reactor, introduce the silicon source into the reactor, and perform at least two stages of deposition. The silicon source enters the porous structure of the spherical skeleton and is transformed into silicon particles to obtain the core.

[0094] S2: Place the core in the reactor, introduce the coating source, and perform coating deposition to form a coating layer on the outer surface of the core, thereby obtaining the silicon-based composite material.

[0095] The present invention introduces a silicon source into a deposition reactor, which causes the silicon source to decompose and disperse in a spherical framework material by heating, and achieves a gradient distribution of silicon particles by performing at least two stages of deposition; then a coating source is added to coat the surface, resulting in a silicon-based composite material with a final gradient silicon distribution.

[0096] In one specific embodiment, the at least two-stage deposition in step S1 includes sequentially performing a first-stage deposition and a second-stage deposition. The temperature of the first-stage deposition is 350℃~500℃, for example, it can be 350℃, 400℃, 450℃ or 500℃. The silicon source flow rate is 0.8L / min~2.2L / min, for example, it can be 0.8L / min, 1.0L / min, 1.2L / min, 1.4L / min, 1.6L / min, 1.8L / min, 2.0L / min or 2.2L / min. The deposition time is 100min~500min, for example, it can be 100min, 200min, 300min, 400min or 500min. The temperature of the second stage deposition is 500℃~700℃, for example, 500℃, 550℃, 600℃, 650℃ or 700℃; the silicon source flow rate is 0.2L / min~1.2L / min, for example, 0.2L / min, 0.4L / min, 0.6L / min, 0.8L / min, 1.0L / min or 1.2L / min; and the deposition time is 50min~300min, for example, 50min, 100min, 150min, 200min, 250min or 300min. Furthermore, the temperature, silicon source flow rate and deposition time of the first stage deposition are not exactly the same as those of the second stage deposition.

[0097] This invention controls the density distribution and particle size of silicon particles by changing the temperature, silicon source flow rate, and deposition time at different stages of silicon source deposition, thereby achieving a density gradient distribution and a particle size gradient distribution of silicon particles within a spherical framework. Specifically, compared to the second stage of deposition, the first stage of deposition has a lower temperature, a higher silicon source flow rate, and a longer deposition time. Therefore, the inner region of the spherical framework exhibits a higher silicon particle density and a smaller particle size.

[0098] The fact that the temperature, silicon source flow rate, and deposition time of the first deposition stage are not exactly the same as those of the second deposition stage means that at least one of the conditions (temperature, silicon source flow rate, and deposition time) of the first and second deposition stages is different.

[0099] The key to silicon source deposition in this invention lies in fluidization state control. By adjusting the silicon source flow rate, the spherical framework is kept in a uniform fluidized state in the fluidized bed, avoiding localized over-reaction. Temperature control must prevent excessively high temperatures from causing rapid decomposition of the silicon source and forming clusters, or excessively low temperatures from leading to incomplete deposition. Specifically, if the temperature is higher, the silicon source flow rate needs to be reduced accordingly to prevent the formation of nano-silicon clusters and ensure gradient distribution. The larger the specific surface area of ​​the spherical framework, the higher the silicon source concentration needs to be to achieve atomic-level dispersion.

[0100] In some embodiments, the deposition technique described in step S1 is not limited to chemical vapor deposition (CVD), but can be a modification technique such as physical vapor deposition (PVD), chemical vapor infiltration (CVI), low-pressure chemical vapor deposition (LPCVD), plasma vapor deposition (PECVD), etc.

[0101] In some embodiments, the present invention can also achieve silicon gradient distribution by placing a spherical skeleton in a silicon source solution and controlling the immersion time.

[0102] In some embodiments, the reactor in step S1 may be a fluidized bed reactor, a CVD rotary kiln, a static bed reactor, a fixed fluidized bed reactor, or a box furnace, etc.

[0103] In some embodiments, the spherical framework in step S1 is preferably a spherical carbon material, which can be a resin-based carbon material or a bio-based carbon material; the size of the spherical carbon material can vary, and the particle size D50 can be 3μm~15μm, preferably 8μm~12μm; specifically, it can be adaptively adjusted according to the target capacity, pore structure and silicon source deposition depth.

[0104] In some embodiments, the silicon source in step S1 includes any one or a combination of at least two of silane, disilane, borane, germanane, methyl orthosilicate, ethyl orthosilicate, or alkoxysilane.

[0105] In some embodiments, the deposition process in step S1 is not limited to using only one silicon source gas. It can also be combined with an inert gas to form a mixed gas. The volume percentage of the silicon source gas in the mixed gas can be 0.5% to 100%, for example, 0.5%, 1.0%, 5.0%, 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 50.0%, or 100%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0106] In some embodiments, the inert gas may be any one or a combination of at least two of nitrogen, argon, helium, or hydrogen.

[0107] In some embodiments, the reactor in step S2 may be a fluidized bed reactor, a CVD rotary kiln, a tube furnace, a vertical reactor, a horizontal reactor, or an atomic layer deposition system (ALD), etc.

[0108] In some embodiments, the coating deposition is not limited to gas phase coating, but can be liquid phase coating or solid phase coating.

[0109] In some preferred embodiments, a CVD rotary kiln is used for vapor phase coating in step S2, wherein the rotation speed of the rotary kiln can be 0~30 rpm, for example, 0 rpm, 10 rpm, 20 rpm or 30 rpm, or more than 30 rpm.

[0110] In some preferred embodiments, a mixture of carbon source gas and inert gas is introduced at a high temperature, causing the carbon source gas to decompose and form a coating layer. The carbon source gas includes acetylene, ethylene, methane, ethane, propane, butane, butadiene, etc.; the coating temperature can be 400℃~800℃, for example, 400℃, 500℃, 600℃, 700℃, or 800℃, or above 800℃, to control the coating layer quality; the coating time can be 30min~1000min, for example, 30min, 60min, 120min, 240min, 500min, or 1000min, or above 1000min; the carbon source gas concentration can be 0~100%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 50%, or 100%, with the remainder being inert gas.

[0111] In some preferred embodiments, the carrier gas is an inert gas such as nitrogen, argon, or helium, and the flow rate can be 0~50L / min, for example, 10L / min, 20L / min, 30L / min or 50L / min, or more than 50L / min, depending on the equipment specifications and material conditions, to ensure uniform coating.

[0112] The technical solution of the present invention will be further illustrated below through specific embodiments.

[0113] Example 1

[0114] This embodiment provides a silicon-based composite material, which includes a core and a coating layer covering the outer surface of the core; the core includes a spherical skeleton and silicon particles, the spherical skeleton has a porous structure, and some of the silicon particles are housed in the porous structure of the spherical skeleton;

[0115] The spherical framework is divided into an inner ring region and an outer ring region covering the surface of the inner ring region. The volume of the inner ring region accounts for 50%. The distribution density of silicon particles in the inner ring region is 2.0 times that in the outer ring region. The particle size of silicon particles in the inner ring region is 1.3 nm, and the particle size of silicon particles in the outer ring region is 2.8 nm. The ratio of the particle size of silicon particles in the inner ring region to that in the outer ring region is 0.46.

[0116] The spherical framework has a particle size D50 of 8 μm and a specific surface area of ​​1800 ± 100 m². 2 / g of spherical porous carbon substrate;

[0117] The coating layer is a carbon coating layer with a thickness of 50 nm;

[0118] The silicon-based composite material has a sphericity of 92%, an angle of repose of 31.5°, and a silicon content of 49.2 wt%.

[0119] The preparation method of the silicon-based composite material described in this embodiment includes the following steps:

[0120] 1500g of particles with a D50 of 8μm and a specific surface area of ​​1800±100m² 2 / g of spherical porous carbon substrate was vacuum dried at 120℃ for 8h. Then, a two-stage deposition process was used. The spherical porous carbon substrate was placed in a reactor and first deposited at 400℃ and 1.5L / min silane flow rate for 300min. Then, the temperature was raised to 600℃ and the silane flow rate was reduced to 0.5L / min to continue deposition for 180min to obtain the core. After deposition, the furnace temperature was maintained at 500℃ and a nitrogen and acetylene mixture with a volume ratio of 3:1 (total flow rate of 17L / min) was introduced for coating for 240min to obtain the silicon-based composite material.

[0121] Example 2

[0122] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0123] In the preparation method of the silicon-based composite material described in this embodiment, except that spherical hard carbon microspheres with a particle size D50 of 10 μm are used as the spherical skeleton, and silane is deposited at 500°C for 200 min at a flow rate of 1.8 L / min, and then deposited for 100 min at a flow rate of 0.6 L / min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0124] Example 3

[0125] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0126] In the preparation method of the silicon-based composite material described in this embodiment, except that a rotary reactor (20 rpm) is used to treat spherical porous carbon with a particle size D50 of 12 μm, and silane is introduced in stages at 480°C, wherein the silane flow rate in the first stage is 1.2 L / min and is continuously introduced for 400 min, the silane flow rate in the second stage is 0.8 L / min and is continuously introduced for 200 min, and then acetylene is introduced in a pulsed manner for coating, so that the adaptability of the obtained silicon-based composite material changes, the rest is the same as in Example 1.

[0127] Example 4

[0128] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0129] In the preparation method of the silicon-based composite material described in this embodiment, except that the spherical porous carbon derived from ZIF-8 is used as the spherical framework, and silane is first deposited at 450°C at a flow rate of 1.5 L / min for 300 min, and then deposited at 450°C at a flow rate of 0.7 L / min for 150 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0130] Example 5

[0131] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0132] In the preparation method of the silicon-based composite material described in this embodiment, except that the silicon gradient distribution is achieved by immersing spherical porous carbon in a 30 vol% siloxane-ethanol solution and controlling the immersion time (the first stage immersion time is 6 h, the second stage immersion time is 2 h, and the silicon-based composite material is coated with acetylene after pyrolysis at 500 °C), the rest is the same as in Example 1.

[0133] Example 6

[0134] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0135] In the preparation method of the silicon-based composite material described in this embodiment, except that after forming a carbon coating layer, a 2nm Al2O3 layer is prepared by atomic layer deposition to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0136] Example 7

[0137] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0138] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 400°C with a flow rate of 1.8 L / min for 360 min, and then deposited at 600°C with a flow rate of 0.4 L / min for 120 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0139] Example 8

[0140] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0141] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 350°C with a flow rate of 2.0 L / min for 550 min, and then deposited at 600°C with a flow rate of 0.3 L / min for 100 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0142] Example 9

[0143] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0144] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 520°C at a flow rate of 1.0 L / min for 240 min, and then deposited at 520°C at a flow rate of 0.8 L / min for 240 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0145] Example 10

[0146] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0147] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 400°C with a flow rate of 1.2 L / min for 260 min, and then deposited at 560°C with a flow rate of 0.8 L / min for 220 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0148] Example 11

[0149] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0150] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 430°C with a flow rate of 1.1 L / min for 230 min, and then deposited at 520°C with a flow rate of 0.9 L / min for 230 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0151] Example 12

[0152] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0153] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 520°C with a flow rate of 1.0 L / min for 220 min, and then deposited at 500°C with a flow rate of 0.9 L / min for 220 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0154] Example 13

[0155] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0156] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 320°C with a flow rate of 1.4 L / min for 300 min, and then deposited at 680°C with a flow rate of 0.6 L / min for 220 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0157] Example 14

[0158] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0159] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 400°C at a flow rate of 1.0 L / min for 90 min, and then deposited at 600°C at a flow rate of 0.8 L / min for 300 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0160] Example 15

[0161] This embodiment provides a silicon-based composite material, and the differences between the silicon-based composite material and Embodiment 1 are shown in Table 1;

[0162] In the preparation method of the silicon-based composite material described in this embodiment, except that silane is first deposited at 400°C with a flow rate of 1.6 L / min for 550 min, and then deposited at 600°C with a flow rate of 0.5 L / min for 60 min to change the adaptability of the obtained silicon-based composite material, the rest is the same as in Example 1.

[0163] Comparative Example 1

[0164] This comparative example provides a silicon-based composite material. The difference between the silicon-based composite material and Example 1 is that the spherical skeleton is replaced with an irregular blocky carbon carrier. The other differences from Example 1 are shown in Table 1.

[0165] The preparation method of the silicon-based composite material described in this comparative example is the same as that in Example 1, except that an irregular blocky carbon carrier is used instead of a spherical skeleton.

[0166] Comparative Example 2

[0167] This comparative example provides a silicon-based composite material, which is obtained by mixing and granulating silicon particles with artificial graphite, wherein the silicon content of the silicon-based composite material is 35 wt%, and the particle size of the silicon particles is 80 nm.

[0168] Comparative Example 3

[0169] This comparative example provides a silicon-based composite material in which the silicon particles do not exhibit density distribution gradients or particle size distribution gradients within a spherical framework. The specific differences from Example 1 are shown in Table 1.

[0170] The preparation method of the silicon-based composite material described in this comparative example is the same as that in Example 1, except that only one silicon deposition was performed, specifically, deposition was carried out at 400°C and 1.5 L / min silane flow rate for 480 min.

[0171] The SEM image of the silicon-based composite material described in Example 1 above is shown below. Figure 1 As shown, the SEM image of the silicon-based composite material described in Comparative Example 1 is as follows. Figure 2 As shown, by Figure 1 and Figure 2 The comparison shows that the silicon-based composite material described in Example 1 has a regular spherical shape, while the silicon-based composite material described in Comparative Example 1 has an irregular block shape with sharp edges. The regular spherical shape of Example 1 has better compressive strength, which is beneficial to improving the volumetric energy density.

[0172] The XRD patterns of the silicon-based composite materials described in Example 1, Comparative Example 1, and Comparative Example 2 are as follows: Figure 3 As shown, the XRD images of Example 1 and Comparative Example 1 are not significantly different, with relatively wide peaks, indicating that the obtained silicon is amorphous silicon. The main difference between the two lies in the morphology of the carrier. Comparative Example 2, on the other hand, shows sharp silicon peaks, indicating that the silicon in Comparative Example 2 has a higher degree of crystallinity.

[0173] The rate performance diagrams of the secondary batteries prepared from the silicon-based composite materials described in Example 1 and Comparative Example 1 are shown in the figure above. Figure 4 As shown, by Figure 4 It can be seen that under 3C conditions, the retention rate of Example 1 was 79.8%, while the retention rate of Comparative Example 1 was only 57.6%.

[0174] The cycle performance diagrams of the secondary batteries prepared from the silicon-based composite materials described in Example 1 and Comparative Example 1 are shown in the figure above. Figure 5 As shown, by Figure 5It can be seen that the cycle retention rate of Example 1 is significantly better than that of Comparative Example 1, and the capacity decay rate is slower. Comparative Example 1 shows more significant capacity decay during long-term cycling.

[0175] The SEM-EDS line scan image of the silicon-based composite material described in Example 1 above is shown below. Figure 6 As shown, by Figure 6 It can be seen that the silicon density in the outer ring region is lower than that in the inner ring region, which verifies the reduction in the distribution density gradient of silicon particles described in this invention.

[0176] In the silicon-based composite materials described in the above embodiments and comparative examples, the ratio of the distribution density of silicon particles in the inner ring region to that in the outer ring region, the particle size of silicon particles in the inner ring region, the particle size of silicon particles in the outer ring region, the ratio of the particle size of silicon particles in the inner ring region to that in the outer ring region, the volume fraction of the inner ring region, the sphericity of the silicon-based composite material, the angle of repose of the silicon-based composite material, and the silicon content in the silicon-based composite material are shown in Table 1.

[0177] Table 1

[0178]

[0179] Since comparative examples 1-3 are not applicable to the density gradient distribution and particle size gradient distribution structures of the present invention, the corresponding content in Table 1 is “ / ”.

[0180] The silicon-based composite material, conductive carbon black, carboxymethyl cellulose, and deionized water obtained in the above examples and comparative examples were mixed to form a homogeneous slurry. The mass ratio of the silicon-based composite material, conductive carbon black, and carboxymethyl cellulose was 95:1.5:3.5. A homogenizer was used for sample preparation at a speed of 2000 rpm for 20 minutes. After sieving, the slurry was uniformly coated onto copper foil and dried in a vacuum drying oven at 90°C. The dried electrode was then rolled and cut into circular electrodes of a specific size, and the electrode mass was recorded. In an argon-atmospheric glove box, a lithium metal sheet was used as the counter electrode, and the obtained electrodes, separator, and gasket were assembled to form a coin cell battery. The electrolyte used in the coin cell battery was a silicon-carbon special electrolyte.

[0181] The obtained coin cells were subjected to electrochemical performance testing under the following specific conditions:

[0182] Capacity: After the coin cell was left to stand at 25±2℃ for 12 hours, it was discharged to 0.005V at a constant current of 0.05C, and then charged to 1.5V at a constant current of 0.05C. The first charge specific capacity was recorded as the first reversible capacity of the silicon-based composite material at 1.5V.

[0183] First-time efficiency: According to the capacity test method above, first-time efficiency = first-charge capacity / first-discharge capacity × 100%.

[0184] 100-cycle retention rate: The button cell battery is cycled 100 times under 0.1C conditions within a voltage range of 0.005V to 1.5V. The 100-cycle retention rate = (100th cycle charge capacity / first cycle charge capacity) × 100%.

[0185] 3C Rate Retention Rate: The coin cell battery was charged and discharged sequentially at 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C rates. 3C rate retention rate = (Charging capacity at 3C / Charging capacity at 0.1C) × 100%. Electrode Expansion Rate after 50 Cycles: The initial electrode thickness T0 was tested. After 50 cycles, the coin cell battery was disassembled and the negative electrode was removed. The electrode thickness T1 after the cycles was tested. Electrode expansion rate after 50 cycles = (T1 - T0) / T0 × 100%.

[0186] The test results are shown in Table 2 below:

[0187] Table 2

[0188]

[0189] As can be seen from Tables 1 and 2 above:

[0190] (1) In the above embodiments, the electrode expansion rate after 50 cycles is less than 62%, and in the preferred embodiments, the electrode expansion rate after 50 cycles is less than 55%. In Example 1, a spherical porous carbon substrate is used as a spherical framework. A silicon density gradient and particle size gradient are achieved through a two-stage deposition process. The material exhibits high capacity, low expansion, and excellent rate performance, with the best overall performance. The first reversible capacity at 1.5V is as high as 1847mAh / g, and the expansion rate after 50 cycles is ≤50%. In Example 2, spherical hard carbon microspheres are used as a spherical framework. Gradient deposition forms a high silicon content. The robust spheres provide a compressive strength advantage, but the conductivity of hard carbon is slightly weak, resulting in a slightly lower first efficiency and cycle retention rate than in Example 1. In Example 3, a uniform gradient distribution of silicon is achieved through a rotating reactor dynamic process. The silicon dispersion is extremely uniform, resulting in a volume expansion rate ≤48% and a cycle life of ≤48%. The following examples illustrate the advantages of different methods: Example 4 uses a nitrogen-doped spherical support derived from MOF as a spherical framework. The gradient design, combined with nitrogen doping, enhances interfacial stability, resulting in an initial efficiency of ≥93% and balanced cycling stability. Example 5 constructs a gradient distribution using a liquid-phase impregnation method, with silicon deeply embedded in the spherical pores. The expansion control is excellent, with an expansion rate of ≤52% after 50 cycles. However, the activity of silicon obtained by the liquid-phase method is relatively low, and the capacity and initial efficiency are the lowest in the series. This example is used to illustrate that the gradient structure of the silicon-based composite material can also be obtained through liquid-phase impregnation pyrolysis and is not intended to limit the preparation method of vapor deposition. Example 6 introduces an alumina composite coating layer on the basis of gradient deposition. The rigid coating layer provides protection, resulting in a retention rate of ≥92% after 100 cycles and an expansion rate of ≤46%. However, the dual interface slightly increases ion migration resistance, leading to a decrease in rate performance.

[0191] (2) As can be seen from Examples 1 and 7-9, the distribution density of silicon particles in the inner ring region and the distribution density of silicon particles in the outer ring region of the present invention should not differ too much, otherwise it will lead to stress concentration, excessive expansion difference, and damage to ion transport channels, thus affecting the first efficiency, cycle and rate performance of the material. However, the distribution density of silicon particles in the inner ring region and the distribution density of silicon particles in the outer ring region should not differ too much either, otherwise it will affect the effect of silicon particle density gradient distribution. As can be seen from Examples 1 and 10-13, if the ratio of the particle size of silicon particles in the inner ring region to the particle size of silicon particles in the outer ring region of the present invention is too large, it will affect the effect of silicon particle size gradient distribution. However, if the ratio of the particle size of silicon particles in the inner ring region to the particle size of silicon particles in the outer ring region is too small, it will affect ion transport and material stability, thus affecting the rate and cycle performance of the battery. As can be seen from Examples 1 and 14-15, the volume ratio of the inner ring region of the present invention will affect the effect of silicon particle density gradient and particle size gradient, preferably within a specific range.

[0192] (3) As can be seen from Example 1 and Comparative Example 1, Comparative Example 1 uses the same process parameters as Example 1, but uses an irregular block carrier. The silicon distribution is uniform and without gradient. During the cycle, the expansion stress is randomly transmitted, resulting in stress concentration between particles and a significant decrease in rate performance. As can be seen from Example 1 and Comparative Example 2, Comparative Example 2 achieves uniform silicon mixing through spray drying. The design without gradient results in prominent silicon agglomeration problems. The structural breakage is accelerated in the later stage of the cycle, and the retention rate after 100 cycles is ≤53%, which cannot take into account both high capacity and low expansion. As can be seen from Example 1 and Comparative Example 3, Comparative Example 3 does not have density gradient distribution and particle size distribution gradient, which cannot avoid silicon breakage and local stress concentration during the cycle, resulting in a decrease in the battery's first efficiency, cycle performance and rate performance, and an increase in electrode expansion rate.

[0193] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A silicon-based composite material, characterized in that, The silicon-based composite material includes a core and a coating layer covering the outer surface of the core; The core includes a spherical framework and silicon particles. The spherical framework has a porous structure, and some or all of the silicon particles are housed within the porous structure of the spherical framework. From the center of the spherical skeleton to the outer surface of the spherical skeleton, the distribution density gradient of the silicon particles decreases, while the particle size gradient of the silicon particles increases.

2. The silicon-based composite material according to claim 1, characterized in that, The spherical skeleton is divided into an inner ring area and an outer ring area covering the surface of the inner ring area. The distribution density of silicon particles in the inner ring area is 1.5 to 3 times that of the distribution density of silicon particles in the outer ring area. The particle size of silicon particles in the inner ring region is ≤2nm, the particle size of silicon particles in the outer ring region is ≤3nm, and the ratio of the particle size of silicon particles in the inner ring region to the particle size of silicon particles in the outer ring region is 0.30~0.

80. In the spherical skeleton, the volume ratio of the inner ring region is 30% to 70%.

3. The silicon-based composite material according to claim 2, characterized in that, The distribution density of silicon particles in the inner ring region is 1.8 to 2.5 times that of silicon particles in the outer ring region; And / or, the particle size of the silicon particles in the inner ring region is 1.2nm~1.8nm, the particle size of the silicon particles in the outer ring region is 2.2nm~3.0nm, and the ratio of the particle size of the silicon particles in the inner ring region to the particle size of the silicon particles in the outer ring region is 0.40~0.

70.

4. The silicon-based composite material according to claim 1 or 2, characterized in that, The silicon particles have a particle size of 1.30 nm to 3.00 nm; And / or, the spacing between the silicon particles is 0.5 nm to 2.0 nm; And / or, the spherical framework includes any one or a combination of at least two of the following: spherical carbon materials, spherical metal oxides, conductive polymer spheres, spherical organic frameworks, or spherical composite materials; And / or, the particle size D50 of the spherical skeleton is 1μm~12μm.

5. The silicon-based composite material according to claim 1 or 2, characterized in that, The coating layer comprises any one or a combination of at least two of carbon, oxides, halides, lithium-containing compounds, or polymers; And / or, the thickness of the coating layer is 20nm~100nm.

6. The silicon-based composite material according to claim 1 or 2, characterized in that, The sphericity of the silicon-based composite material is ≥70%; And / or, the angle of repose of the silicon-based composite material is ≤38°; And / or, in the silicon-based composite material, the silicon content is 10wt%~80wt%.

7. A method for preparing a silicon-based composite material as described in any one of claims 1-6, characterized in that, The preparation method includes the following steps: A spherical framework is placed in a reactor, and a silicon source is introduced into the reactor for at least two stages of deposition. The silicon source enters the porous structure of the spherical framework and is transformed into silicon particles to obtain the core. The core is placed in a reactor, a coating source is introduced, and coating deposition is performed to form a coating layer on the outer surface of the core, thus obtaining the silicon-based composite material.

8. The preparation method according to claim 7, characterized in that, The at least two depositional stages include sequentially performing a first depositional stage and a second depositional stage. The temperature of the first stage deposition is 350℃~500℃, the silicon source flow rate is 0.8L / min~2.2L / min, and the deposition time is 100min~500min; The second stage deposition temperature is 500℃~700℃, the silicon source flow rate is 0.2L / min~1.2L / min, and the deposition time is 50min~300min; The temperature, silicon source flow rate, and deposition time of the first deposition stage are not exactly the same as those of the second deposition stage; The temperature of the first deposition stage is lower than that of the second deposition stage, and / or the silicon source flow rate of the first deposition stage is higher than that of the second deposition stage, and / or the deposition time of the first deposition stage is longer than that of the second deposition stage.

9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the silicon-based composite material as described in any one of claims 1-6, or the silicon-based composite material prepared by the preparation method as described in claim 7 or 8.

10. A secondary battery, characterized in that, The secondary battery includes the silicon-based composite material as described in any one of claims 1-6, or the silicon-based composite material prepared by the preparation method described in claim 7 or 8, or the negative electrode sheet as described in claim 9.